The Effect of Sub-Lethal Exposure of Sodium Dodecyl Sulfate on Zebrafish (Danio rerio) Larvae Development - Siti Rahmah, Ahmad (Universiti Malaysia Sarawak (UNIMAS), 2014)
Sodium dodecyl sulfate (SDS) is widely used as surfactant in household products such as toothpaste, shampoos, bubble foams, cosmetic and detergent. However, SDS may also have detrimental effects after being discharged into water. SDS can flow into aquatic ecosystem, where it can exert a variety of physiologically effects in living organisms including fish. This study therefore aimed to investigate the effect of sub-lethal exposure SDS on zebrafish larvae development. The exposure of SDS was tested on zebrafish embryo within seven day. The sub-lethal exposure were determined to be in range 9.5 mg/L to 15 mg/L. At concentration 10 mg/L of SDS, there were consistent result that effect the temporal development. Hatching rate, free swim rate and survival rate of 10 mg/L SDS was significantly reduced by 37.7% (p<0.05), 19.65% (p<0.05), and 53% (p<0.005) respectively. Besides that, the phenotypic deformities was observed at the zebrafish that under treatment which include pericardia! edema, yolk sac edema, vertebrate bent and tail bent. This study revealed that sub-lethal exposure of SDS has capability for detrimental effect on aquatic organism. Therefore, sodium dodecyl sulfate could seriously damage the development of zebrafish.